2012
DOI: 10.1016/j.ibmb.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

FoxO inhibits juvenile hormone biosynthesis and vitellogenin production in the German cockroach

Abstract: The transcription factor Forkhead-box O (FoxO) is the main transcriptional effector of the Insulin Receptor/Phosphatidylinositol 3-kinase (InR/PI3K) pathway. In a situation of nutrient restriction, the pathway is inactive and FoxO translocates to the nucleus to exert its transcriptional action. In starved females of the cockroach Blattella germanica, the reproductive processes, and in particular the synthesis of juvenile hormone in the corpora allata and that of vitellogenin in the fat body, are arrested. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…Suppression of FOXO significantly increased JHAMT expression, while reducing bmm expression (Figure 5a). Therefore, FOXO reduction increases JH biosynthesis through upregulation of JHAMT, as predicted by Suren-Castillo et al (2012). Since the promoter region of bmm was reported to harbor several FOXO response elements in Drosophila (Wang et al, 2011), reduction of bmm expression following FOXO reduction is not unexpected.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Suppression of FOXO significantly increased JHAMT expression, while reducing bmm expression (Figure 5a). Therefore, FOXO reduction increases JH biosynthesis through upregulation of JHAMT, as predicted by Suren-Castillo et al (2012). Since the promoter region of bmm was reported to harbor several FOXO response elements in Drosophila (Wang et al, 2011), reduction of bmm expression following FOXO reduction is not unexpected.…”
Section: Resultsmentioning
confidence: 93%
“…Recent studies show that the JH signaling may intersect with the IIS pathway through the Chico (an adaptor protein that interacts with the insulin-like peptide receptor) and/or FOXO (the downstream transcriptional regulator of the insulin pathway) proteins or may even directly alter the expression of specific ILPs (Parthasarathy and Palli, 2011; Sheng et al, 2011). Genetic suppression of chico or FOXO reduces or increases JH biosynthesis, respectively (Tu et al, 2005; Suren-Castillo et al, 2012). Unlike the IIS pathway, JH signaling is unique to insects.…”
Section: Introductionmentioning
confidence: 99%
“…These effects could be rescued by injection of bovine insulin. Studies in the mosquito, Aedes aegypti and the cockroach, Blattella germanica , have demonstrated feedback of the ILP/TOR pathways on the JH biosynthetic activity of the CA, thus placing JH downstream of the ILP/TOR pathway [60][62]. In starved B. germanica , silencing FOXO resulted in increased Vg mRNA levels in the fat body and a rise in JH biosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…10) suggest that the insulin/insulin-like growth factor signaling (IIS), JH, and vitellogenin (Vg) pathways, known to regulate reproduction in adult insects (47)(48)(49)(50)(51), play predominant roles in modulating larval development in response to environmental cues. A well-known example illustrating the role of these pathways is the caste fate of the female brood (queen or worker) in the honey bee Apis mellifera (52)(53)(54)(55)(56)(57)(58).…”
mentioning
confidence: 99%